The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/1471-0528.14967
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal sleep practices and late stillbirth – findings from a stillbirth case‐control study

Abstract: ObjectiveTo report maternal sleep practices in women who experienced a stillbirth compared with controls with ongoing live pregnancies at similar gestation.DesignProspective case‐control study.SettingForty‐one maternity units in the United Kingdom.PopulationWomen who had a stillbirth after ≥ 28 weeks’ gestation (n = 291) and women with an ongoing pregnancy at the time of interview (n = 733).MethodsData were collected using an interviewer‐administered questionnaire that included questions on maternal sleep prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
96
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 31 publications
6
96
0
4
Order By: Relevance
“…Indeed, the Auckland study 4 reported higher odds of long sleep duration, one or fewer times getting up to use the bathroom, and regular daytime naps in the stillbirth group compared with controls, although short sleepers were also more common in the stillbirth group. This latter study was remarkably similar to the recent Midlands and North of England Stillbirth Study, 7 which also reported frequent daytime napping, one or fewer awakenings to use the bathroom, and both long and short sleep as being more common in the stillbirth group. Short sleep-but not long sleep-was more common in the stillbirth group in the New Zealand multicenter stillbirth case-control study, 6 which also found a higher odds for not getting up to go to the toilet.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Indeed, the Auckland study 4 reported higher odds of long sleep duration, one or fewer times getting up to use the bathroom, and regular daytime naps in the stillbirth group compared with controls, although short sleepers were also more common in the stillbirth group. This latter study was remarkably similar to the recent Midlands and North of England Stillbirth Study, 7 which also reported frequent daytime napping, one or fewer awakenings to use the bathroom, and both long and short sleep as being more common in the stillbirth group. Short sleep-but not long sleep-was more common in the stillbirth group in the New Zealand multicenter stillbirth case-control study, 6 which also found a higher odds for not getting up to go to the toilet.…”
Section: Discussionsupporting
confidence: 84%
“…4 This case-control study demonstrated that women who reported settling to sleep in the supine position on the last night of pregnancy were significantly more likely to experience stillbirth, even after accounting for other factors (aOR 2.54 [95% CI 1.04-6.18]). [5][6][7] These studies have also noted differences in maternal sleep duration and number of awakenings between stillbirths and live births. This finding has now been observed in three further studies using similar methodologies with similar effect sizes.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A cross‐sectional study in Ghana reported similar outcomes, with supine position associated with an increased risk for low birth weight and stillbirth . The Midland and North of England Stillbirth Study also reported that going to sleep in the supine position significantly increased the risk of stillbirth …”
Section: Introductionmentioning
confidence: 99%
“…12 The Midland and North of England Stillbirth Study also reported that going to sleep in the supine position significantly increased the risk of stillbirth. 13 This is particularly relevant in the context of the triple risk model proposed by Warland and Mitchell,14 which describes stillbirth as the outcome of interactions among: (1) maternal factors, such as age, body mass index (BMI, calculated as weight in kilograms divided by the square of height in meters), smoking, or alcohol consumption; (2) fetal and placental influences, such as intrauterine growth restriction The aim of the study was to assess if maternal sleep position during pregnancy had an effect on maternal and/or fetal autonomic regulation, as measured by HRV parameters.…”
mentioning
confidence: 99%